An assessment of the mediating role of self-esteem in the relationship between body image disturbance and psychological distress among undergraduates - Joshua Oludare Ogunsemi; Adah Temple Tamuno-Opubo; Oluseyi Abiodun Alakija (Journal of Indonesian Psychological Science (JIPS), 2026)
Psychological distress is a common mental health concern among university students and may be influenced by body image difficulties and low self-esteem. However, limited research has examined how self-esteem explains the relationship between body image disturbance and psychological distress among Nigerian undergraduates. This study investigated whether self-esteem mediates the relationship between body image disturbance and psychological distress among undergraduates in selected universities in Nigeria. A cross-sectional survey was conducted among 401 undergraduates from three universities in Osun State, Nigeria. Standardised measures of body image disturbance, self-esteem, and psychological distress were administered, and the data were analysed using correlation, regression, and mediation analyses. Findings showed that higher body image disturbance was associated with lower self-esteem and greater psychological distress, while higher self-esteem was linked to lower psychological distress. Self-esteem partially explained the relationship between body image disturbance and psychological distress, suggesting that students with negative body image may experience greater distress partly because of reduced self-worth. The study highlights the importance of addressing self-esteem in university mental health interventions and contributes to the limited literature on body image and psychological well-being among Nigerian undergraduates. KEY WORDS: body image;self-esteem; psychological distress; university students; Nigeria Copyright ©2026. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0